42nd AIAA Fluid Dynamics Conference and Exhibit 2012
DOI: 10.2514/6.2012-2841
|View full text |Cite
|
Sign up to set email alerts
|

Low Reynolds Number Flow Dynamics of a Thin, Flat Airfoil with Elastically Mounted Trailing Edge

Abstract: Direct numerical simulations were performed to study the effect of an elastically mounted trailing edge actuator on the unsteady flow over a plunging, thin airfoil at Reynolds number of 14700 based on the chord length. The goal is to investigate potential benefits of flow-induced passive actuation of the trailing edge to the lift and drag characteristics of flapping MAV wings. The trailing edge, of 30% the chord length, is hinged to the wing using a torsion spring. It may undergo flow induced rotation resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…For example, Heathcote and Gursul [31] demonstrated using PIV and hydrodynamic force measurements that a heaving airfoil with a deformable trailing edge generates stronger trailing edge vortices (TEVs), which results in an enhanced thrust coefficient when compared to a purely rigid airfoil. The direct numerical simulation results by Apte and Base [9], where the trailing edge flexibility is modeled using spring dynamics and allowed to be influenced by the fluid-structure interactions, are in good agreement with the experimental results of Heathcote and Gursul. Apte and Base concluded that in order to maximize the propulsion efficiency, the natural frequency of the trailing edge should be similar in magnitude to the heaving frequency of the airfoil.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…For example, Heathcote and Gursul [31] demonstrated using PIV and hydrodynamic force measurements that a heaving airfoil with a deformable trailing edge generates stronger trailing edge vortices (TEVs), which results in an enhanced thrust coefficient when compared to a purely rigid airfoil. The direct numerical simulation results by Apte and Base [9], where the trailing edge flexibility is modeled using spring dynamics and allowed to be influenced by the fluid-structure interactions, are in good agreement with the experimental results of Heathcote and Gursul. Apte and Base concluded that in order to maximize the propulsion efficiency, the natural frequency of the trailing edge should be similar in magnitude to the heaving frequency of the airfoil.…”
Section: Introductionsupporting
confidence: 72%
“…Growing aero/marine applications for energy harvesting and propulsion have advanced research into animal locomotion [1][2][3][4][5]. The flow physics of swimming and flying animals has received significant attention mostly in the context of developing bioinspired micro-air vehicles and oscillating flow energy harvesters [6][7][8][9][10]. Many animals, including fish, insects, and birds, exploit complex oscillatory motion for highly efficient maneuvering and aero/hydrodynamic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minor peaks occur when the pitching angle is decreasing and as the upstroke in heaving just begins. At this point in the cycle, it is speculated that a leading edge vortex (LEV) forms on the bottom surface of the wing due to the heaving motion reversal, as described by Apte et al (2012). The LEV creates a negative lift by decreasing the pressure at the bottom surface relative to that of the upper surface.…”
Section: Rigid Wingmentioning
confidence: 97%
“…Improving the aerodynamic performance of small, thin wings enhances the propulsion efficiency used in surveillance and rescuing missions. The drawback with thin airfoils in low Reynolds number flows is that at large angles of attack, leading edge flow separation occurs resulting in a Kelvin-Helmholtz flow instability [1,2] . Flow separation leads to a sudden change in lift and drag, which can cause a rapid decrease in aerodynamic performance.…”
Section: Introductionmentioning
confidence: 99%